Eosinophilic esophagitis: comorbidities and atopic disease in Nevada. Issue 5 (12th February 2020) - Anderson, Julia; Moonie, Sheniz; Hogan, Mary Beth; Scherr, Rebecca; Allenback, Gayle
Summary: Eosinophilic esophagitis (EoE) is a rare, immune-mediated illness. We aimed to examine the comorbidities and sensitization patterns associated with an EoE diagnosis in Nevada. The study goal was two-fold: to determine the most common EoE comorbidities and sequela in the state of Nevada using healthcare utilization records across all settings and to determine the most common food and aeroallergens in histologically positive EoE pediatric patients using clinical sensitization data. Esophageal obstruction/stricture was the most frequently reported diagnosis in adults with EoE (29.5%). Among pediatrics, the highest ranking comorbidities included asthma (13.4%); diseases of the stomach, duodenum, and intestine (7.26%); allergies (7.01%); and gastroesophageal reflux disease (GERD) (3.69%). Additionally, the top sensitizations reported in histologically positive EoE patients were largely pollen related (82.9%). Atopic disease and specifically food allergens are commonly reported as comorbid conditions with EoE in the literature. However, our clinical pediatric data set from this study revealed that aeroallergen sensitizations far exceeded that of food allergens (82.9% aero-positive vs. 17.1% dood positive). The high presence of esophageal stricture/obstruction in adults could be indicative of late diagnosis; in addition, the aeroallergen sensitization in children could suggest different clinical management techniques necessary may be needed for this disease. Education among healthcare providers regarding the presence of aeroallergen sensitization in this population may result in earlier diagnoses and help reduce morbidity and the cost from this disease.